Задача з розрахунку виявлення помилки передачі даних за модулем HC-05 Bluetooth - Ткачов, Д. Р. (ХНУРЕ, 2025)
This paper explores the probability of undetected errors in HC-05 Bluetooth data transmission, assessing efficiency based on speed and bandwidth. It examines the impact of CRC length on error detection and estimates channel capacity using Shannon’s formula.
Keywords: помилка передачі даних; HC-05 Bluetooth